2017
DOI: 10.1039/c7ra02726e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light scattering effect of wrinkled transparent conductive ITO thin film

Abstract: Indium tin oxide (ITO) plays an important role due to its high transparency and high conductivity in various optoelectronic thin-film devices. However, ITO has the drawback of mechanical fragility, limiting its development. Wrinkling has been considered a powerful tool for improving the flexibility and surface properties of thin films, but wrinkled ITO has not been reported so far. In this work, we fabricate uniform wrinkles on ITO and systematically study the properties of the wrinkled ITO in optics, electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Formation of buckles (wrinkles) on a thin film attached to a compliant substrate has received considerable attention due to the advancement of flexible electronics, [1][2][3][4][5] optoelectronics and photovoltaics, [6][7][8][9][10][11] and various functional devices, [12][13][14][15][16] as well as the development of self-organizing mechanisms. [17][18][19][20][21] Buckling can be triggered by direct application of an in-plane compressive strain, as schematically shown in Figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of buckles (wrinkles) on a thin film attached to a compliant substrate has received considerable attention due to the advancement of flexible electronics, [1][2][3][4][5] optoelectronics and photovoltaics, [6][7][8][9][10][11] and various functional devices, [12][13][14][15][16] as well as the development of self-organizing mechanisms. [17][18][19][20][21] Buckling can be triggered by direct application of an in-plane compressive strain, as schematically shown in Figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…A wrinkled structure has been shown to increase light harvesting efficiency for organic PV layers (Lipomi et al, 2011;Kim et al, 2012;Ji et al, 2018) and improved light extraction in organic light-emitting diodes (Ji et al, 2018). In the case of "hard" PV and/or conducting layers such as silicon, perovskite, and indium tin oxide, various ways of fabricating them onto an instability-driven wrinkled base structure, for the purpose of enhancing light trapping (Ram et al, 2017;Bush et al, 2018;Schauer et al, 2018;Zhang et al, 2018) or scattering (Wang C. et al, 2017), have been reported. An added benefit of the wrinkled structure is the possible improvement in deformability in stretchable electronics (Wang B. et al, 2017); thus enabling their potential deployment in fabrics and on curved or uneven surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low crystallinity can increase transparency [4] . Consequently, intra grain boundary scattering phenomenon cannot be ignored [5] .…”
Section: Results and Analysesmentioning
confidence: 99%
“…Meanwhile, the intensity of the scattered light is inversely proportional to the fourth power of the wavelength of the incident light. That is to say, the shorter the wavelength is, the stronger the scattering is and the lower the transmissivity is due to the Rayleigh scattering formula (2)(3)(4)(5).…”
Section: Results and Analysesmentioning
confidence: 99%